Imagining the Commoning Library: Alter-Neoliberal Pedagogy in Informational Capitalism - Dimitris Soudias (Journal of Digital Social Research)
The ascent of neoliberalism and informational capitalism has been largely successful in privatizing and re-regulating state-subject-market relations in ways that treat them “as if” they are a market situation. Here, we observe both the increasing commodification of digital forms of knowledge, as well as the commodification of the access to this knowledge. As predominantly non-commercial spaces, libraries serve the vital function of deflecting these developments. In this article, I argue for going one step further and imagining libraries as institutionalized and pedagogical spaces that can negotiate and transgress their institutional limits vis-à-vis public and private resources, discourses, policies, and technologies for the purpose of furthering the commons. In so doing, libraries serve as alter-neoliberal pedagogies, which democratize the construction and deconstruction of knowledge, as well as the access to them. Here, alternative literacies, ways of learning, and ways of being can be prefigured in practice. In imagining these conceptual potentialities of academic and public libraries, this article sets forth an initial agenda toward the commoning library.